Price fixing from the Islamic Jurisprudence & Economics perspective - Sayyed Reza Husseini (جستارهای اقتصادی, 2005)
Fixing Price and its related policy is an important issue which isdiscussed not only in jurisprudential and traditional texts, but also ineconomics. With an emphasis on interdisciplinary approach, thearticle tends to consider government fixing prices of goods andservices from the epistemological jurisprudence & economicsperspective. Even at the situation of monopoly and hoarding up, thegovernment is not authorized for fixing prices, as the article tries tofocus on. To come up with the discussion and achieving acomprehensive understanding over it, nature of price and its positionin economic system is also considered here.